Palaeoeskimo dwellings in Greenland: A survey - Andreasen, Claus (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2003)
AbstractIn Greenland, Palaeoeskimo dwellings are mostly concentrated in the north and northeast parts of the island. Some are found in the southeast, in the west (from Nuuk to Disko Bay), and in the northwest (Inglefield Land and Washington Land). During the entire period, Palaeoeskimo dwellings show an emphasis on an axial element. In the Early Palaeoeskimo period (Saqqaq and Independence I) the fireplace is a separate square box inside two parallel rows of flags or boulders. Cooking and/or seething stones are common during Saqqaq and rare in Dorset. In Late Saqqaq, a shift in dwelling style to a platform-like dwelling is indicated by material from the Disko Bay region. During Independence II, the external borders of the axial feature often extend towards the front of the dwelling and may display "wings" at one or both ends. Late Dorset is only found in Northwest Greenland where the material from Inglefield Land documents the presence of at least four dwelling types with a clear axial element in the more substantial ruins.